Production of bio-fertilizer from landfill leachate through vermicomposting with rice husk addition as a bulking agent - Mohammed Zainul Ariff, Zaharuddin (2017)
Landfill leachate is a very complex high-strength wastewater which contains suspended and dissolved materials removed from the decomposing waste in the landfill body. It consists of soluble organic and inorganic constituents. It is highly toxic and has detrimental effects on the environment. Landfill leachate is generally characterized by extremely high concentrations of biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammoniacal-nitrogen, and heavy metals (e.g. Cd, Cu, and Zn). However, it is also a source of nutrients, which consists of high organic matters (e.g. nitrogen, phosphorus, potassium and trace elements) that make leachate has a potential to be developed as a bio-fertilizer. The vermicomposting process by using rice husk as the additive found to be an effective way to reduce the toxicity of the leachate and stabilize the nutrients level for the leachate to be applied safely on soil. Therefore, a study was conducted to identify the amount of nitrogen-N, phosphorus-P, and potassium-K composition in the leachate. N, P, and K content in the leachate can be utilized through vermicomposting process to produce high and better quality of bio-fertilizer. Parameters that would be monitor along the composting process are the temperature, compost mass ratios, pH and moisture content to produce high quality of final product that could serve as a soil amendment in the shortest time. The matured end-product also will be undergoes a phytotoxicity assays on the growth of eggplants to test whether it can be used as a bio-fertilizer. Finding from this work is crucial for landfill leachate management as to minimize its pollution risk to the environment. An economic estimation showed that the production cost of leachate as fertilizer is low and that an interesting profit margin could be obtained through the commercialization of composted leachate as a bio-fertilizer.